2013
DOI: 10.1093/ntr/nts339
|View full text |Cite
|
Sign up to set email alerts
|

Pilot RCT Results of Stop My Smoking USA: A Text Messaging–Based Smoking Cessation Program for Young Adults

Abstract: To address the lack of smoking cessation programs available to young adults, Stop My Smoking (SMS) USA, a text messaging-based smoking cessation program, was developed and pilot tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 34 publications
1
88
0
5
Order By: Relevance
“…126 Although the intervention produced significantly higher abstinence rates at 4 weeks, these differences were not sustained at 3 months.…”
Section: Recent Studiesmentioning
confidence: 94%
“…126 Although the intervention produced significantly higher abstinence rates at 4 weeks, these differences were not sustained at 3 months.…”
Section: Recent Studiesmentioning
confidence: 94%
“…A recent meta-analysis of 13 studies using SMS in smoking cessation counseling suggested that SMS based interventions generally increased quit rates when compared with no intervention (25). Another study investigating SMS based intervention for smoking cessation in young adults aged 18-25 years showed an increase in smoking cessation in the short-term (4 weeks after cessation), but the data on long-term results was not sustained and it was inconclusive (26). The study of Naughton et al (27) showed similar quit rates with SMS intervention for the short-term (4 and 8 weeks after quit date), but the 6th month long-term results favored SMS intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Study results consistently report this method as an acceptable and effective way to communicate and provide advice and support to service users (Cole-Lewis & Kershaw, 2010). Research evaluating TM interventions among non-pregnant individuals who smoke has demonstrated their effectiveness and success in increasing cessation rates, improving adherence to pharmacotherapy, and maintaining high participation (Brendryen & Kraft, 2008;Free et al, 2009;Free et al, 2011;Haug, Meyer, Schorr, Bauer & John, 2009;Haug et al, 2013;Obermayer, Riley, Asif & Jean-Mary, 2004;Rodgers et al, 2005;Whittaker et al, 2009;Ybarra et al, 2013).…”
Section: Introductionmentioning
confidence: 87%